Hubungan Tingkat Pengetahuan dengan Nilai Empati pada Mahasiswa Fakultas Kedokteran Unika Atma Jaya, Jakarta - Darren Gosal; Yeremias Jena (Jurnal Perkotaan, 2017)
Empathy is one of the virtues that should be owned by health care providers. In the doctor– patient relationship, empathy enables health care providers to win not only the confidence of the patients, but also assisting them to accept their state of illness and disease. As to the fact that medical students have a high knowledge of empathy in line with the study periods, empathic relation is often absent in doctor–patient relationship. This study is intended to look at the relationship between the length of studies and the knowledge of empathy. This cross- sectional study applied Baron-Cohen Empathy Quotient to collect data from 98 respondents at Atma Jaya School of Medicine, Atma Jaya Catholic University of Indonesia, academic years of 2013 (third year) and 2015 (the first year). The study revealed that 49 respondents have a higher level of empathy knowledge and 49 others at the lower one. Among the higher knowledge of empathy, 73.47% (n=36) had lower knowledge of empathy compared to 26.53% (n=13) at the higher one. Among the lower knowledge of empathy, 91.84% (n=45) had lower knowledge of knowledge compared to 8.16% (n=4) at the higher one. A total of 76.47% respondents with a higher knowledge of empathy (n=17) were the third year students (academic year 2013), whereas the 23.52% are the first year students (academic year 2015). This study has proven the relation between the length studies (academic years) with the knowledge level of empathy.